Urban Planning and Industrial Territories Landscape Analysis - Adilov, Z. Kh.; Zakirova М. Sh. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses measures to mitigate and prevent environmental damage to industrial areas in urban planning and landscaping, and outlines ways to mitigate environmental problems.